Cold-Strontium Laser in the Superradiant Crossover Regime - Matthew A. Norcia; James K. Thompson (Physical Review X, 2016)
Today’s narrowest linewidth lasers are limited by mirror motion in the reference optical resonator used to stabilize the laser’s frequency. Recent proposals suggest that superradiant lasers based on narrow dipole-forbidden transitions in cold alkaline earth atoms could offer a way around this limitation. Such lasers operating on transitions with linewidth of order mHz are predicted to achieve output spectra orders of magnitude narrower than any currently existing laser. As a step towards this goal, we demonstrate and study a laser based on the 7.5-kHz linewidth dipole-forbidden ^{3}P_{1} to ^{1}S_{0} transition in laser-cooled and tightly confined ^{88}Sr. We can operate this laser in the bad-cavity or superradiant regime, where coherence is primarily stored in the atoms, or continuously tune to the more conventional good-cavity regime, where coherence is primarily stored in the light field. We show that the cold-atom gain medium can be repumped to achieve quasi-steady-state lasing. We also demonstrate up to an order of magnitude suppression in the sensitivity of laser frequency to changes in cavity length, verifying a key feature of the proposed narrow linewidth lasers.